The 14th International Conference on Human Retrovirology: HTLV and related retroviruses (July 1–4, 2009; Salvador, Brazil) - Willems Luc (Retrovirology, 2009)
Abstract The "14th International Conference on Human Retrovirology: HTLV and Related Retroviruses" was held in Salvador, Bahia, from July 1st to July 4th 2009. The aim of this biennial meeting is to promote discussion and share new findings between researchers and clinicians for the benefit of patients infected by human T-lymphotropic virus (HTLV). HTLV infects approximately 15–20 million individuals worldwide and causes a broad spectrum of diseases including neurodegeneration and leukemia. The scientific program included a breadth of HTLV research topics: epidemiology, host immune response, basic mechanisms of protein function, virology, pathogenesis, clinical aspects and treatment. Exciting new findings were presented in these different fields, and the new advances have led to novel clinical trials. Here, highlights from this conference are summarized.